The Shape Shifting Story of Reticulocyte Maturation - Ovchynnikova, Elina; Aglialoro, Francesca; von Lindern, Marieke; van den Akker, Emile (Frontiers in Physiology, 2018)
The final steps of erythropoiesis yielding erythrocytes involves some unique cellular processes including enucleation, reorganization of membrane proteins and the cytoskeleton to become biconcave erythrocytes, a process that is surprisingly poorly understood. In vitro protocols currently produce reticulocytes rather than biconcave erythrocytes. In addition, immortalized lines and iPSC-derived erythroid cell suffer from low enucleation and suboptimal final maturation potential. In light of the increasing prospect to use in vitro produced erythrocytes as (personalized) transfusion products or as therapeutic delivery agents, the mechanisms driving this last step of erythropoiesis are in dire need of resolving. Here we review the illusive last steps of reticulocyte maturation with an emphasis on protein sorting during the defining steps of reticulocyte formation during enucleation and maturation.